2018
DOI: 10.1088/1741-4326/aaec97
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of defects by the presence of hydrogen in tungsten: simultaneous W-ion damaging and D-atom exposure

Abstract: The possible mutual influence and synergistic effect between defect production and the presence of hydrogen isotopes in the crystal lattice of tungsten is studied. For this purpose, we perform modelling of experimental data where polycrystalline tungsten samples were in one case sequentially irradiated by 10.8 MeV tungsten ions followed by low energy deuterium exposure and in the other case simultaneously irradiated by tungsten ions while exposed to deuterium atoms. Modeling of the measured deuterium depth pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 56 publications
2
37
0
Order By: Relevance
“…We can conclude from this that no effect was observed in the atom case at 450 K due to the shallow penetration depth (Fig. 14b) which was also the conclusion from modeling the atom data in [7]. Therefore, high concentration of mobile atoms increases the speed of filling of the available traps and consequently increases stabilization of the defects.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…We can conclude from this that no effect was observed in the atom case at 450 K due to the shallow penetration depth (Fig. 14b) which was also the conclusion from modeling the atom data in [7]. Therefore, high concentration of mobile atoms increases the speed of filling of the available traps and consequently increases stabilization of the defects.…”
Section: Discussionsupporting
confidence: 65%
“…where R is the reflection coefficient, Γ is the ion flux, d is the average ion range, D is the diffusion constant and δ W is the tungsten volume density. [7]. At 450 K c S is two orders of magnitude smaller than for the ion case.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This is in good agreement from past results reported by Hodille et al [13] but still lower than the results reported by Frauenfelder. This can be explained by the fact that Frauenfelder conducted his experiment at a much higher temperature of about a 1000 K where the surface D coverage was much lower than in our case where the experiment was done at 600 K. Some DFT calculations [36] and also our own experimental results [37] indicate that the chemisorption energy of the surface depends on the D coverage, increasing with falling coverage. From our recent results [37] we see that indeed at higher exposure temperatures E ef f bulk + E ch = 1.9 eV which is much closer to the value reported by Frauenfelder.…”
Section: Simulationmentioning
confidence: 56%